LU-HF, IN-SITU SR AND PB ISOTOPE AND TRACE ELEMENT SYSTEMATICS FOR MANTLE ECLOGITES FROM THE DIAVIK DIAMOND MINE: EVIDENCE FOR PALEOPROTEROZOIC SUBDUCTION BENEATH THE SLAVE CRATON, CANADA - Schmidberger S.S.; Simonetti A.; Heaman L.M.; Creaser R.A.; Whiteford S. (My University, 2007)
Lu-Hf, Sm-Nd and in-situ clinopyroxene Sr and Pb isotope systematics, and mineral major and in-situ trace element compositions were obtained for a suite of non-diamond and diamond-bearing eclogites from the Diavik kimberlites (A154; 55 Ma old), Slave craton (Canada). Temperature estimates of last equilibration in the lithosphere for the non-diamond-bearing Diavik eclogites define two groups; low-temperature (800-1050 °C) and high-temperature eclogites (1100-1300 °C). Most diamond-eclogites indicate temperatures similar to those of the high-temperature eclogites. Isotopic and major and trace element systematics for the non-diamond- and diamond-bearing eclogites indicate overlapping chemical compositions suggesting similar rock formational histories. Calculated whole rock major and trace element abundances using chemical and modal abundances for constituent minerals exhibit broad similarities with mafic cumulates from ophiolite sequences. Most importantly the calculated whole rock eclogite compositions display positive Sr and Eu anomalies, typically interpreted as the result of plagioclase accumulation in cumulate rocks of oceanic crust sequences. Initial whole rock Hf isotopic values and in-situ Sr isotope data from clinopyroxene grains provide evidence that the eclogites were derived from precursor rocks with depleted mantle isotope characteristics. These combined results support the interpretation that the eclogites from Diavik represent remnants of subducted oceanic crust. Lu-Hf isotope systematics indicate that the oceanic protolith for the eclogites formed in the Paleoproterozoic at ~ 2.1 Ga, which is in agreement with the in-situ Pb isotope data from clinopyroxene. This result also corroborates the ~ 2.1 Ga Lu-Hf model ages recorded by mantle zircons from eclogite found within the Jericho kimberlite in the northern Slave Province (~ 200 km northwest of Diavik). The results from both studies indicate a link between eclogite formation and Paleoproterozoic subduction of oceanic lithosphere along the present-day western margin of the Archean Slave craton. © 2006 Elsevier B.V. All rights reserved.
Keywords: ECLOGITE; ISOTOPES; LASER ABLATION ANALYSIS; SLAVE CRATON; SUBDUCTION; TRACE ELEMENTS; Archean; Paleoproterozoic; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская